2022
DOI: 10.1370/afm.2859
|View full text |Cite
|
Sign up to set email alerts
|

Revitalizing Primary Care, Part 2: Hopes for the Future

Abstract: Part 1 of this essay argued that the root causes of primary care's problems lie in (1) the low percent of national health expenditures dedicated to primary care and (2) overly large patient panels that clinicians without a team are unable to manage, leading to widespread burnout and poor patient access. Part 2 explores policies and practice changes that could solve or mitigate these primary care problems.Initiatives attempting to improve primary care are discussed. Diffuse multi-component initiatives-patient-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 77 publications
0
10
0
2
Order By: Relevance
“…Nos recherches en Ontario ont permis de constater que la patientèle prise en charge par des cabinets prodiguant des soins en équipe était plus susceptible de recevoir les soins recommandés pour les maladies chroniques 6 et moins susceptible d’utiliser les services d’urgence 7 . La répartition des soins dans une équipe peut aussi accroître le bien-être au travail des prestataires de soins de santé 8 et, lorsqu’exécutée correctement, accroître la patientèle dont un médecin de famille peut prendre soin 9 . Des problèmes d’effectifs similaires ont poussé des leaders d’opinion des États-Unis et du Royaume-Uni à réclamer un recours élargi à des équipes interprofessionnelles comme élément de solution 9 , 10 .…”
unclassified
See 1 more Smart Citation
“…Nos recherches en Ontario ont permis de constater que la patientèle prise en charge par des cabinets prodiguant des soins en équipe était plus susceptible de recevoir les soins recommandés pour les maladies chroniques 6 et moins susceptible d’utiliser les services d’urgence 7 . La répartition des soins dans une équipe peut aussi accroître le bien-être au travail des prestataires de soins de santé 8 et, lorsqu’exécutée correctement, accroître la patientèle dont un médecin de famille peut prendre soin 9 . Des problèmes d’effectifs similaires ont poussé des leaders d’opinion des États-Unis et du Royaume-Uni à réclamer un recours élargi à des équipes interprofessionnelles comme élément de solution 9 , 10 .…”
unclassified
“…La répartition des soins dans une équipe peut aussi accroître le bien-être au travail des prestataires de soins de santé 8 et, lorsqu’exécutée correctement, accroître la patientèle dont un médecin de famille peut prendre soin 9 . Des problèmes d’effectifs similaires ont poussé des leaders d’opinion des États-Unis et du Royaume-Uni à réclamer un recours élargi à des équipes interprofessionnelles comme élément de solution 9 , 10 . D’après un sondage récent mené auprès des médecins de famille de la Colombie-Britannique, les prestataires de soins de santé classent la possibilité de travailler au sein d’une équipe et le financement direct des postes des équipes comme des priorités pour une réforme des soins primaires 11 .…”
unclassified
“…rimary care faces major headwinds; time pressures, administrative demands, burnout, low reimbursement, and poor alignment of payment systems with patient needs are just some of the contributors. 1,2 Yet a high-functioning primary care system is often recognized as essential to healthy communities. 3 In the quest for equitable, highquality accessible and available health care, primary care must often rapidly evolve to meet societal needs and take on additional roles.…”
mentioning
confidence: 99%
“…7 Sharing the care in a team can also enhance joy in work for clinicians 8 and, when done right, could increase the number of patients a family physician can care for. 9 Similar primary-care workforce challenges have led thought leaders in the United States and United Kingdom to call for expansion of interprofessional teams as part of the solution. 9,10 A recent survey of family physicians in British Columbia found that physicians ranked options to be in a team and direct funding for team roles as priorities for primary care reform.…”
mentioning
confidence: 99%